2022
DOI: 10.1088/1361-6471/ac9226
|View full text |Cite
|
Sign up to set email alerts
|

A false vacuum Skyrme model for nuclear matter

Abstract: The low energy regime of Quantum Chromodynamics (QCD) presents enormous challenges due to its large coupling. Effective field theories, like the Skyrme model, are useful approaches to study properties of strong interaction at hadronic scales. We propose a Skyrme-type model with a self-dual sector and that treats the density of the baryonic charge as a self-interacting fluid. The dynamics reduces to Coleman’s false vacuum problem for a scalar field that is a fractional power of that density. The main result is that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Substituting the axial Anzatz ( 28), ( 29) into the Hamiltonian of the Skyrme-Maxwell model (25) and into the Lagrangian (9), we obtain…”
Section: Axially Symmetric Ansatz and Effective Lagrangianmentioning
confidence: 99%
See 1 more Smart Citation
“…Substituting the axial Anzatz ( 28), ( 29) into the Hamiltonian of the Skyrme-Maxwell model (25) and into the Lagrangian (9), we obtain…”
Section: Axially Symmetric Ansatz and Effective Lagrangianmentioning
confidence: 99%
“…The most radical version of the BPS Skyrme theory is constructed via truncation of the model, it contains only a sixth-order derivative term, which is the topological current density squared, and a potential [21,22]. It has been also suggested to consider a modification of the Skyrme model which supports self-duality equations [23][24][25]. Another direction is related with extensions of the Skyrme model via inclusion of higher-order derivative terms [21,22,[39][40][41][42][43], with various modifications of the potential and couplings.…”
Section: Introductionmentioning
confidence: 99%
“…The Skyrme model, a (3+1)-dimensional nonlinear field theory of pions, is a model of hadrons and is supposed to be the most promising and long-lived effective model in the low-energy domain of quantumchromodynamics (QCD). The skyrmions, the topological solitons in the Skyrme model, well describe not only the standard hadrons and nuclei, but also structures of the dense nuclear matter [1][2][3][4] and the neutron star [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In principle, terms such as also explicitly break chiral symmetry. It is found that this term introduces a false vacuum to the Skyrme model [25][26][27][28] in addition to the vacuum of QCD. Therefore, it is interesting to study the skyrmion properties with respect to this false vacuum, which is not only relevant to hadron physics but may also help us un-derstand the cosmological phase transition process [29][30][31].…”
mentioning
confidence: 99%
“…When this false vacuum is added, the Skyrme model admits a false meta-stable skyrmion configuration [32], which can decay due to the tunneling effect [33], consequently causing the decay of the false vacuum [25]. In addition, with the appropriate choice of the false vacuum potential, the experimental values of radii and binding energies for a wide range of nuclear mass numbers can be calculated with good precision [26][27][28].…”
mentioning
confidence: 99%